Portraying Son Preference Through Family Dynamics in Elif Shafak's Honour - Hilman Maulana Ibrahim; Adelie Grace Marianne litaay (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines the representation of son preference in Elif Shafak's novel Honour (2012), which traces three generations of a Turkish immigrant family across rural Turkey and London.